Recent progress in the effect of ferroptosis of HSCs on the development of liver fibrosis - Tang, Rui; Luo, Jing; Zhu, Xiaoxia; Miao, Pengyu; Tang, Hong; Jian, Yue; Ruan, Sibei; Ling, Feng; Tang, Mingxi (Frontiers in Molecular Biosciences, 2023)
Fibrosis is a common pathological process that must undergo for multiple chronic liver diseases to develop into cirrhosis and liver cancer. Liver fibrosis is regulated by various cytokines and signaling pathways in its occurrence and development. Ferroptosis is an important mode of cell death caused by iron-dependent oxidative damage, and is regulated by iron metabolism and lipid peroxidation signaling pathways. In recent years, numerous studies have shown that ferroptosis is closely related to liver fibrosis. As the main material secreted by the extracellular matrix, hepatic stellate cell (HSCs) are a general concern in the development of liver fibrosis (LF). Therefore, targeting HSCs ferroptosis against LF is crucial. This review describes the current status of treating liver fibrosis by inducing HSCs ferroptosis, that would aid studies better understand the current knowledge on ferroptosis in HSCs and the future research direction in this field.